Investigation of the high and very high cycle fatigue behaviour of continuous fibre reinforced plastics by conventional and ultrasonic fatigue testing. (22nd March 2017) - Flore, D.; Wegener, K.; Mayer, H.; Karr, U.; Oetting, C.C.
Abstract: At present the fatigue behaviour of glass fibre reinforced plastics (GFRP) and the corresponding failure mechanisms are rarely investigated in the very high cycle fatigue (VHCF) regime. This is due to a lack of testing equipment fitted to the specific properties of fibre reinforced plastics. To obtain comprehensive knowledge about the fatigue behaviour of GFRP in the VHCF regime, ultrasonic fatigue testing equipment has been applied for cyclic tension testing of GFRP for the first time. Ultrasonic fatigue testing (UFT) reduces the testing time in comparison to conventional techniques by a factor of 100. UFT is used to determine the fatigue strength of GFRP in the range of 10 6 − 10 9 cycles. Data obtained by UFT is compared to fatigue data generated using a conventional servo-hydraulic device at low frequencies of 10 Hz. Both data sets agree very well which indicates the suitability of UFT for this material.